ANALISIS BAHASA INDONESIA PENENTU KEBERHASILAN BELAJAR SISWA KELAS IX DI SMP NEGERI 1 BANDUNGAN - Wati, Rini Pralistya (FPIPSKR Universitas PGRI Semarang, 2024)
SMP Negeri I Bandungan is one of the junior high schools in Semarang Regency which has a strategic role in preparing human resources. Therefore, the use of Indonesian determines the creation of good learning outcomes, considering that Indonesian is a better language of instruction and is quickly understood for students. In accordance with the problems discussed in the research, this research has general and specific objectives. The general aim of the research is to analyze and determine the contribution of motivation, competence and learning satisfaction to student efforts. SMP Negeri I Bandungan, Semarang district. Both jointly and individually. Specifically, this research is aimed at the following: to analyze and determine the contribution of motivation, competence and learning satisfaction. The results of the research show that a total of 129 questionnaires were distributed and all of the questionnaires were returned. The verification results showed that only 125 were declared valid. Thus, the data in this study used 125 samples as research subjects. The F test is carried out to determine the correlation of several independent variables with the dependent variable together. The calculation results show that the F value obtained is 44.784 with a significant p0.05. Together, these results identify significant confirmation of the learning outcomes of class IX students at SMP Negeri I Bandungan. Student competency and learning satisfaction together with student learning is 46.4%. The remaining 53.6% is determined by other variations of this model.